Enhanced T-cell activation and chemokine-associated function in CD14-positive cells from venous sinus blood in sub-acute cerebral venous sinus thrombosis - Chang, Yu-Zhou; Song, Yu-Qi; Zhu, Hao-Yu; Zhang, Jia-Rui; Fu, Xi-Guang; Wang, Yi-Long; Dong, Ke-Hui; Jiang, Chu-Han; Mo, Da-Peng; Zhang, Yu-Peng (Frontiers in Cell and Developmental Biology, 2024)
BackgroundPatients with sub-acute cerebral venous sinus thrombosis experience (SA.CVST) severe symptoms compared to two other venous sinus-related diseases, including chronic cerebral venous sinus thrombosis (C.CVST) and idiopathic intracranial hypertension (IIH).ObjectiveThis study aimed to determine whether the different immune reactions in different venous sinuses are related.MethodsStagnant blood in the cerebral venous sinuses was extracted by passing a microcatheter and CD14-positive cells were sorted by magnetic beads and subjected to RNA-seq sequencing.ResultsCompared to patients with IIH, 128 genes were significantly down-regulated and 373 genes were significantly up-regulated in the sub-acute CVST samples. The functions of these genes were mainly focused on “immune response”, “T cell activation” and “plasma membrane”. Gene Set Enrichment Analysis (GSEA) showed T cell survival and activation-related function significantly unregulated in sub-acute CVST. On the other hand, there were 366 genes down-regulated in chronic CVST and 75 genes up-regulated in chronic CVST. In functional annotation, these differently expressed genes were enriched in the “extracellular region”, “chemokine-mediated signaling pathway” and “immune response”. GSEA analysis confirmed that chemokine-related functions were all up-regulated in sub-acute CVST and monocyte-macrophage adhesion functions were also significantly up-regulated.ConclusionThis study suggested the CD14-positive created an activated immune response in sub-acute CVST.